PENGARUH PEMAHAMAN PAJAK DAN KESADARAN WAJIB PAJAK TERHADAP KEPATUHAM PAJAK UMKM (Studi Kasus Toko Pakaian di Toraja Utara) - Prima Panggalo; Dwibin Kannapadang; Agustinus Mantong (JURNAL ILMIAH EDUNOMIKA, 2025)
One of the biggest contributors to state income comes from the tax sector. As a source of state finances where taxes have a budget function, the government tries to put as much money as possible into the state treasury through tax revenue. However, the level of tax compliance is still low, this is due to the lack of understanding and awareness of the community, especially MSME owners. Therefore, the authors conducted a study and research on the Effect of Tax Understanding and Taxpayer Awareness on Tax Compliance in Micro, Small and Medium Enterprises (MSMEs) Clothing stores in North Toraja Regency. The type of research used in this research is quantitative research. The sampling technique used was purposive sampling. The data analysis technique used in this study uses statistical data processing tools, namely SPSS version 26. The data used in this study are primary data and secondary data. The results of this study indicate that the effect of tax understanding and taxpayer awareness has a positive and significant effect on tax compliance of MSMEs clothing stores in North Toraja Regency. Keywords: Tax Understanding, Taxpayer Awareness, Tax Compliance, MSMEs